2016
DOI: 10.5194/se-2016-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a numerical workflow based on μ-CT-imaging for the determination of capillary pressure-saturation-specific interfacial area relationship in two-phase flow pore-scale porous media systems: A case study on Heletz sandstone

Abstract: Abstract. In this case study, we present the implementation of a FEM-based numerical pore-scale model that enables to track and quantify the propagating fluid-fluid interfacial area on highly complex μ-CT obtained geometries. Special focus is drawn to the reservoir specific capillary pressure (pc)- wetting phase saturation (Sw)- interfacial area (awn)- relationship. The basis of this approach are high resolution μ-CT images representing the geometrical characteristics of a georeservoir sample. The successfully… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The exhibited ranges of effective porosity, 2 intrinsic permeability, and tortuosity of the sandstone were 0.189-0.219 3 , 325-3070 mD, and 1.31-2.6, respectively, depending on the method of analysis. 28 A mesh of the CT-scanned pore space from Tatomir et al 28 used in Peche et al 29 , was also used in this study (Fig. 1).…”
Section: D-image Analysis: Extracting a Network Representation Of Heletz Sandstonementioning
confidence: 99%
“…The exhibited ranges of effective porosity, 2 intrinsic permeability, and tortuosity of the sandstone were 0.189-0.219 3 , 325-3070 mD, and 1.31-2.6, respectively, depending on the method of analysis. 28 A mesh of the CT-scanned pore space from Tatomir et al 28 used in Peche et al 29 , was also used in this study (Fig. 1).…”
Section: D-image Analysis: Extracting a Network Representation Of Heletz Sandstonementioning
confidence: 99%
“…Experimental data could then be generated for the true capillary pressure, saturation, and fluid‐fluid interfacial area for a large number of states accurately and precisely under equilibrium conditions with the results interpreted in an inclusive and robust manner. These conditions have been compromised in certain respects in virtually all studies (Chan & Govindaraju, ; Chen et al, ; Joekar‐Niasar & Hassanizadeh, ; Karadimitriou et al, ; Peche et al, ). In effective experiments, the need exists for high‐resolution imaging that requires extended periods of time to capture the range of media considered, the size of the systems investigated, the number of states that can be observed, the time allowed for equilibrium to be achieved, and in many cases the monitoring of interfacial curvature needed to compute the true capillary pressure.…”
Section: Role Of Interfacial Areamentioning
confidence: 99%
“…Many attempts conclude that the HG hypothesis is appropriate and helpful, although some have concluded that only a reduction in hysteretic behavior can be achieved by including interfacial area in the relation (Cheng et al, ; Held & Celia, ; Joekar‐Niasar, Prodanovic, et al, ; Karadimitriou et al, ; Porter et al, ). The issue is considered open and work has continued over recent years using consistently improving methods (Godinez‐Brizuela et al, ; Nikooee et al, ; Paustian, ; Peche et al, ; Sivanesapillai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Peche et al (2016) and Henkel et al (2016) present a novel workflow for the determination of the interfacial surface area of a CO 2 -brine system as a case study on Heletz sandstone, and additionally a comparison of modeling results with an experimental CO 2 study. Last but not least, Mukunoki et al (2016) present research of CT investigations of structures in unconsolidated sand, relevant for environmental engineering.…”
Section: Content and Highlights Of This Special Issuementioning
confidence: 99%